Revenue effects of practice nurse-led care for chronic diseases - Iles, R.; Eley, D.; Hegney, Desley; Patterson, E.; Young, J.; Del Mar, C.; Synnott, R.; Scuffham, P. (CSIRO Publishing, 2014)
Objective: To determine the economic feasibility in Australian general practices of using a practice nurse (PN)-led care model of chronic disease management. Methods: A cost-analysis of item numbers from the Medicare Benefit Schedule (MBS) was performed in three Australian general practices, one urban, one regional and one rural. Patients (n =254; >18 years of age) with chronic conditions (type 2 diabetes, hypertension, ischaemic heart disease) but without unstable or major health problems were randomised into usual general practitioner (GP) or PN-led care for management of their condition over a period of 12 months. After the 12-month intervention, total MBS item charges were evaluated for patients managed for their stable chronic condition by usual GP or PN-led care. Zero-skewness log transformation was applied to cost data and log-linear regression analysis was undertaken. Results: There was an estimated A$129 mean increase in total MBS item charges over a 1-year period (controlled for age, self-reported quality of life and geographic location of practice) associated with PN-led care. The frequency of GP and PN visits varied markedly according to the chronic disease. Conclusions: Medicare reimbursements provided sufficient funding for general practices to employ PNs within limits of workloads before the new Practice Nurse Incentive Program was introduced in July 2012.